Companion to aesthetics / edited by David Cooper - "Cooper, David (ed.)" (Oxford, 1999)
This reference series, centered on analytic philosophy but also covering important aspects of the continental tradition and of non-Western philosophies, is made up of a number of volumes each dealing with a particular subject area. Taken together the series offers a comprehensive survey of philosophy as a whole. The entries in each volume combine summarized information on names, terms and movements and each essay is also supported by a selective bibliography.
Keywords: Aesthetics